Adibah Amin’s selected english prose writings a study of ‘Panopticism’ - Ahmad Zaki, Farah Akmar; Quayum, Mohammad Abdul (translator) (IIUM Press, International Islamic University Malaysia, 2017)
This book aims to illustrate Adibah Amin’s of the influence of social conditioning and normalisation on people’s thoughts and behaviourin both volumes of As I Was Passing (2007) as well as in Glimpses: Cameos of Malaysian Life (2008). This is achieved through three objectives: first, highlighting her representation of the procedures of panopticism, which include spatial distributions, coding of actions, accumulation of time and combination of forces; second, identifying her representation of the instruments of panopticism, which involve hierarchical observation, normalising judgement and examination; third, addressing the four panoptic characteristics fabricated out of the abovementioned procedures and instruments, namely cellular, organic, genetic and combinatory. To pursue these three objectives, the book employs Michel Foucault’s formulation of ‘panopticism’, a theory of social conditioning and normalisation by way of disciplinary techniques and mechanisms. While Adibah Amin’s humorous style of writing is what frequently renders her English anecdotes interesting, this should not be the blanket description defining her works as it will eclipse her astute and critical observations of people’s routines, tendencies, norms and idiosyncrasies. Adibah Amin has revealed in her selected narratives that people are prone to be both the object and the effect of conditioning and normalising procedures and instruments. It is hoped that this book will give Adibah Amin the recognition that she truly deserves and make people aware of the various serious issues that she deals with in her narratives, albeit with humour.